Greening business : research, theory, and practice - Worthington, Ian (Colección de libros electrónicos de ULoyola, 2013)
Environmental protection has increasingly become a business issue at both the strategic and operational level for businesses of all sizes and across all continents. Greening Business is a comprehensive and highly contemporary analysis of the business/natural environment interface. Supported by numerous examples of current environmental practices in industry and commerce, the book examines why, when, and how businesses have responded to the growing pressures from governments, citizens, and other stakeholders to improve on their environmental performance. Focusing on the firm as the primary unit of analysis, the book examines the major drivers of corporate ecological responsiveness and critically investigates the nature and range of business responses in both theory and practice. It offers a detailed analysis of the contested business case for corporate greening, using insights from current strategy and management theory, including the resource-based view of the firm, and discusses the ways in which a firm can incorporate its concern for environmental protection into its day-to-day operations and decisions and through its strategic posture. It concludes with a discussion of the notion of the ecologically sustainable enterprise.